The Impact Of The Instant Digital Era On Impulsive Behavior And Patience Waiting For The Turn Of Grade Iii Students Of Sdn 76 Bengkulu City - Syaza Zahrotul Mutoharoha; Alda Ratika Anggraini; Yosi Yulizah; Ahmad Suradi (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The development of the digital era that is instantaneous affects children's behavior patterns, including the ability to control themselves and patience in waiting for their turn. This study aims to describe the impact of the instant digital era on impulsive behavior and patience waiting for the turn of grade III students of SDN 76 Bengkulu City. The research uses a qualitative descriptive approach with research subjects in the form of grade III students, classroom teachers, and classroom learning situations. The data collection technique was carried out through observation and semi-structured interviews with teachers. Data analysis is carried out through the stages of data reduction, data presentation, and inductive conclusions. The results showed that students tended to show impulsive behavior, such as wanting to get a turn immediately, cutting off friends' conversations, showing impatience when queuing, and having difficulty waiting for learning results that took place gradually. These findings suggest that exposure to digital media that provides quick response and instant gratification contributes to decreased ability to delay desires and low tolerance for the waiting process. However, the ability to control impulses and wait for their turn can still be developed through discipline habituation, assistance in the use of gadgets by parents, and learning strategies that train self-regulation at school. Therefore, synergy between schools and families is needed in shaping children's character of patience and self control in the digital era.